Coronavirus, Force Majeure and Impact on Commercial Contracts - Mugisha, Frank (Mkts., Inc, 2020)
Looking at the supply chain disruption caused by the Covid-19 pandemic, it is likely that performances under many contracts will be delayed, interrupted, or even cancelled. Counterparties (especially suppliers) to such contracts may seek to delay and/or avoid performance (or non-performance liability) of their contractual obligations and/or terminate contracts, either because Covid-19 has legitimately prevented them from performing their contractual obligations, or because they are seeking to use it as an excuse to extricate themselves from an unfavorable deal. Further, companies may not be able to perform their obligations under their customer agreements because of their suppliers’ non-performance and may in turn seek to delay and/or avoid performance (or liability for non-performance) of their contractual obligations and/or terminate contracts. Parties may also cite Covid-19 as a basis for renegotiation of price or other key contractual provisions (e.g. volume of materials exported from or imported into affected areas due to shifts in supply and demand). In this context, it is important to determine if Covid-19 and the presidential/Government directives (guidelines) will be considered as a ‘force majeure’ event
Keywords: Coronavirus; Commercial Contracts; Force Majeure